"That's What Music Is About—It Strikes a Chord": Proposing a Queer Method of Listening to the Lives and Music of LGBTQs. (1st April 2016) - Wasserbauer, Marion
Abstract: This article proposes and discusses a queer methodology for oral history research in the LGBTQ community. Music and musical mementos function as the basis of these oral histories, allowing the narrators to guide me through their stories about LGBTQ identity and music. In line with theories of the queer archive and feminist research methods, a collaborative and situated multimedia research approach with a focus on music is suggested. By means of four diverse narrators' stories, I discuss how this methodology works in practice.